Uncertainty Estimation for the Brillouin Frequency Shift Measurement Using a Scanning Tandem Fabry–Pérot Interferometer - Patrice Salzenstein; Thomas Y. Wu (Micromachines, 2023)
The expanded uncertainty of the measured Brillouin scattering shift frequencies is essential in assessing the measurements of parameters of various materials. We describe the general operation principles of a Brillouin light scattering (BLS) spectrometer with a high-power laser and a scanning tandem Fabry–Pérot interferometer (TFPI) for material characterization. Various uncertainty components have been analyzed for the BLS spectrometer following the Guide to the Expression of Uncertainty in Measurement (GUM). The expanded relative uncertainty in the measured Brillouin frequency shift of 15.70 GHz for polymethyl methacrylate (PMMA) was estimated to be 0.26%. The calculated Brillouin frequency shift (based on material properties of PMMA) was determined to be 15.44 GHz with expanded relative uncertainty of 2.13%. It was shown that the measured and calculated Brillouin frequency shifts for PMMA agree within their expanded uncertainties. The TFPI-based BLS spectrometer can be used to measure the longitudinal modulus of materials with an expanded uncertainty of 1.9%, which is smaller than that of the ultrasonic velocity-based method (estimated to be 2.9%).